Incidence, therapy, and outcome in the management of chronic subdural hematoma in Switzerland: a population-based multicenter cohort study - El Rahal, Amir; Beck, Jürgen; Ahlborn, Peter; Bernasconi, Corrado; Marbacher, Serge; Wanderer, Stefan; Burkhardt, Jan-Karl; Daniel, Roy Thomas; Ferrari, Andrea; Hausmann, Oliver; Kamenova, Maria; Kothbauer, Karl; et al. (Frontiers in Neurology, 2023)
Background Chronic subdural hematoma (cSDH) is a disease affecting mainly elderly individuals. The reported incidence ranges from 2.0/100,000 to 58 per 100,000 person-years when only considering patients who are over 70 years old, with an overall incidence of 8.2–14.0 per 100,000 persons. Due to an estimated doubling of the population above 65 years old between 2000 and 2030, cSDH will become an even more significant concern. To gain an overview of cSDH hospital admission rates, treatment, and outcome, we performed this multicenter national cohort study of patients requiring surgical treatment of cSDH. Methods A multicenter cohort study included patients treated in 2013 in a Swiss center accredited for residency. Demographics, medical history, symptoms, and medication were recorded. Imaging at admission was evaluated, and therapy was divided into burr hole craniostomy (BHC), twist drill craniostomy (TDC), and craniotomy. Patients' outcomes were dichotomized into good (mRS, 0–3) and poor (mRS, 4–6) outcomes. A two-sided t-test for unpaired variables was performed, while a chi-square test was performed for categorical variables, and a p-value of <0.05 was considered to be statistically significant. Results A total of 663 patients were included. The median age was 76 years, and the overall incidence rate was 8.2/100,000. With age, the incidence rate increased to 64.2/100,000 in patients aged 80–89 years. The most prevalent symptoms were gait disturbance in 362 (58.6%) of patients, headache in 286 (46.4%), and focal neurological deficits in 252 (40.7%). CSDH distribution was unilateral in 478 (72.1%) patients, while 185 presented a bilateral hematoma with no difference in the outcome. BHC was the most performed procedure for 758 (97.3%) evacuations. CSDH recurrence was noted in 104 patients (20.1%). A good outcome was seen in almost 81% of patients. Factors associated with poor outcomes were age, GCS and mRS on admission, and the occurrence of multiple deficits present at the diagnosis of the cSDH. Conclusion As the first multicenter national cohort-based study analyzing the disease burden of cSDH, our study reveals that the hospital admission rate of cSDH was 8.2/100,000, while with age, it rose to 64.2/100,000. A good outcome was seen in 81% of patients, who maintained the same quality of life as before the surgery. However, the mortality rate was 4%.